2003
DOI: 10.1002/ijc.11241
|View full text |Cite
|
Sign up to set email alerts
|

MHC class I‐deficient metastatic tumor variants immunoselected by T lymphocytes originate from the coordinated downregulation of APM components

Abstract: Previous reports from our group indicated that the MHC class I phenotype of metastatic lung colonies produced by a mouse fibrosarcoma tumor clone (B9) were, depending on the immune status of the host, MHC class I negative in immunocompetent mice and MHC class I positive in immunodeficient athymic nude/nude mice. Now we report the identification of the molecular alterations responsible for the changes of MHC class I molecules in both situations. Metastatic nodes were analyzed for the mRNA level of H-2 class I a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
56
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 25 publications
6
56
1
Order By: Relevance
“…It is an intriguing and consistent finding that Tpn is downregulated in many human carcinomas, such as breast cancer (8,9), melanoma (10), colorectal carcinoma (11), and both small cell and non -small cell lung carcinoma (12), as well as mouse cancers, such as mouse fibrosarcoma (13) and mouse melanoma (14). Remarkably, in human colorectal cancers, Tpn is more frequently lost than TAP1, LMP2, and LMP7 (11), suggesting that the loss of Tpn could be a key event in overcoming immune surveillance in these tumors.…”
mentioning
confidence: 86%
“…It is an intriguing and consistent finding that Tpn is downregulated in many human carcinomas, such as breast cancer (8,9), melanoma (10), colorectal carcinoma (11), and both small cell and non -small cell lung carcinoma (12), as well as mouse cancers, such as mouse fibrosarcoma (13) and mouse melanoma (14). Remarkably, in human colorectal cancers, Tpn is more frequently lost than TAP1, LMP2, and LMP7 (11), suggesting that the loss of Tpn could be a key event in overcoming immune surveillance in these tumors.…”
mentioning
confidence: 86%
“…β2m is an integral component, of MHC class I expression, is synthesized in the CNS, and plays a critical role in neural development. (42) Many tumors, including brain tumors, are known to down regulate class I MHC expression to avoid immune surveillance. (42) Although the extent of this surveillance for CNS-localized malignancies is unclear, the fact that β2m is up-regulated in the context of MHC class I down-regulation suggests that it may be a positive feedback mechanism or pro-tumorigenic function.…”
Section: Validation Of Previously Identified and Discovery Of New Bimentioning
confidence: 99%
“…(42) Many tumors, including brain tumors, are known to down regulate class I MHC expression to avoid immune surveillance. (42) Although the extent of this surveillance for CNS-localized malignancies is unclear, the fact that β2m is up-regulated in the context of MHC class I down-regulation suggests that it may be a positive feedback mechanism or pro-tumorigenic function. (43,44) The latter hypothesis is supported by recent findings about β2m tumor promoting activities in prostate cancer through activation of osteogenic proteins, (45) some of which, including SPARC, are also seen in our analysis.…”
Section: Validation Of Previously Identified and Discovery Of New Bimentioning
confidence: 99%
“…However, whether MHC class I molecules have a positive or negative role in tumor patients' survival remains controversial. Certain studies have reported that MHC class I loss has poor outcomes due to its impact on antigen presentation to T-lymphocytes and CTLs (5,6). By contrast, other reports have revealed that MHC class I loss may improve patients' survival through activating natural killer (NK) cell function (7,8).…”
Section: Introductionmentioning
confidence: 99%